2020
DOI: 10.1016/j.clgc.2019.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Pazopanib-Induced Liver Toxicity in Patients With Metastatic Renal Cell Carcinoma: Effect of UGT1A1 Polymorphism on Pazopanib Dose Reduction, Safety, and Patient Outcomes

Abstract: Treatment of patients with metastatic renal cell carcinoma with pazopanib has been associated with an increased probability of developing liver toxicity in the presence of polymorphisms in the gene UGT1A1 (uridine diphosphate glucuronosyltransferase 1A1), leading to treatment interruptions and permanent discontinuation. We have demonstrated that UGT1A1-guided dosing can manage pazopanib-induced liver toxicity and also that UGT1A1 polymorphisms are associated with improved outcomes, despite pazopanib interrupti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…Preceding pharmacogenetic studies have reported association between Gilbert syndrome uridine diphosphate glucuronosyltransferase 1A1 (UGT1A1) variants and hyperbilirubinemia in patiens treated with pazopanib and sunitinib [ 38 , 39 ]. The UGT1A1 enzyme is inhibited by pazopanib, and patients carrying the UGT1A1∗28 allele have been identified to be at risk of hyperbilirubinemia [ 40 ]. Xu et al reported on a potential association between the presence of a mutation of the hemochromatosis gene (HFE) on chromosome 6 and human leukocyte antigen B∗57:01 (HLA-B∗57:01) carrier status, and ALT elevation in pazopanib-treated patients [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preceding pharmacogenetic studies have reported association between Gilbert syndrome uridine diphosphate glucuronosyltransferase 1A1 (UGT1A1) variants and hyperbilirubinemia in patiens treated with pazopanib and sunitinib [ 38 , 39 ]. The UGT1A1 enzyme is inhibited by pazopanib, and patients carrying the UGT1A1∗28 allele have been identified to be at risk of hyperbilirubinemia [ 40 ]. Xu et al reported on a potential association between the presence of a mutation of the hemochromatosis gene (HFE) on chromosome 6 and human leukocyte antigen B∗57:01 (HLA-B∗57:01) carrier status, and ALT elevation in pazopanib-treated patients [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…39 Similarly, the findings by Henriksen et al revealed that UGT1A1*28 improved the PFS and OS in metastatic renal cell carcinoma. 40 In contrast, the study by Yamaguchi et al confirmed that UGT1A1*6 and *28 were shown to be related to a shorter OS in advanced gastric cancer when irinotecan monotherapy was used as a third-line treatment. 41 In the present study, the K-M survival analysis revealed that patients with mutant UGT1A1*6 (P = 0.146) or *28 (P = 0.195) genotypes had a non-significant inferior OS compared to those with the wild genotype.…”
Section: Dovepressmentioning
confidence: 93%
“…69 A recent retrospective analysis of pazopanib-treated patients who had metastatic RCC and treatment-related hepatotoxicity demonstrated that UGT1A1 poor metabolizers required frequent dosing interruptions. 70 Those authors proposed that UGT1A1 assessment to guide dosing could improve the management of pazopanib-induced liver toxicity. The FDA cautions that UGT1A1 poor metabolizers may be at risk for hyperbilirubinemia but does not suggest a dose modification in the label.…”
Section: Functional Ugt1a1 Inhibitors: Nilotinib and Pazopanibmentioning
confidence: 99%
“…Genome‐wide association studies (GWAS), including a large analysis conducted in patients with RCC (n = 1099), have also demonstrated a significant relationship between elevated bilirubin levels and UGT1A1 variants in patients treated with pazopanib ( P = 2.9 × 10 −17 ) 69 . A recent retrospective analysis of pazopanib‐treated patients who had metastatic RCC and treatment‐related hepatotoxicity demonstrated that UGT1A1 poor metabolizers required frequent dosing interruptions 70 . Those authors proposed that UGT1A1 assessment to guide dosing could improve the management of pazopanib‐induced liver toxicity.…”
Section: Ugt1a1: Implications For Newer Therapiesmentioning
confidence: 99%
See 1 more Smart Citation